Transformasi pengelolaan finansial UMKM The Bos Cafe melalui pendampingan manajemen keuangan berkelanjutan - Qanita Nur Adilah; Arta Widya Ayu Prameswari; Lexzatara Safadila; Santi Karomah; Muharrommah Muharrommah; Yuniar Elsa Habibillah; Moh. Ilham Izamri; Moh. Fikri Haikal; Sofwan Arif Hudzaifi; Ach. Fauzan; Fadali Rahman (Penamas: Journal of Community Service, 2026)
This community service activity aimed to analyze the financial management practices of The Bos Cafe MSME and provide sustainable financial management assistance to support business continuity. The activity was conducted on May 19, 2026, for one day and involved one MSME partner, namely The Bos Cafe. The method employed was a descriptive qualitative approach through participatory field observations, direct interviews, educational sessions, discussions, and financial management mentoring. The observation results indicated that financial management had been carried out through daily cash recording and the use of a manual cash book. However, several challenges were still identified, including inconsistent transaction recording, limited business capital, and the mixing of personal and business finances. The mentoring activities included education on separating personal and business finances, systematic recording of transactions, preparation of simple financial statements, and business cash flow management. The evaluation results showed that the partner understood the importance of separating personal and business finances, maintaining regular transaction records, managing cash flow, and preparing simple financial statements to support business decision-making.